Comparison of UAV and WorldView-2 imagery for mapping leaf area index of mangrove forest - Tian, Jinyan; Wang, Le; Li, Xiaojuan; Gong, Huili; Shi, Chen; Zhong, Ruofei; Liu, Xiaomeng (International journal of applied earth observation and geoinformation, 2017)
•Mangrove forest LAI was mapped with UAV multispectral image for the first time.•Interference from background and species in mapping LAI was firstly eliminated by UAV ScNDVI.•Drawbacks and advantages between UAV and WV2 were firstly compared in mangrove LAI retrieval.•Overall performance of UAV is better than WV2 due to its ultra-high spatial resolution. Unmanned Aerial Vehicle (UAV) remote sensing has opened the door to new sources of data to effectively characterize vegetation metrics at very high spatial resolution and at flexible revisit frequencies. Successful estimation of the leaf area index (LAI) in precision agriculture with a UAV image has been reported in several studies. However, in most forests, the challenges associated with the interference from a complex background and a variety of vegetation species have hindered research using UAV images. To the best of our knowledge, very few studies have mapped the forest LAI with a UAV image. In addition, the drawbacks and advantages of estimating the forest LAI with UAV and satellite images at high spatial resolution remain a knowledge gap in existing literature. Therefore, this paper aims to map LAI in a mangrove forest with a complex background and a variety of vegetation species using a UAV image and compare it with a WorldView-2 image (WV2). In this study, three representative NDVIs, average NDVI (AvNDVI), vegetated specific NDVI (VsNDVI), and scaled NDVI (ScNDVI), were acquired with UAV and WV2 to predict the plot level (10×10m) LAI. The results showed that AvNDVI achieved the highest accuracy for WV2 (R2=0.778, RMSE=0.424), whereas ScNDVI obtained the optimal accuracy for UAV (R2=0.817, RMSE=0.423). In addition, an overall comparison results of the WV2 and UAV derived LAIs indicated that UAV obtained a better accuracy than WV2 in the plots that were covered with homogeneous mangrove species or in the low LAI plots, which was because UAV can effectively eliminate the influence from the background and the vegetation species owing to its high spatial resolution. However, WV2 obtained a slightly higher accuracy than UAV in the plots covered with a variety of mangrove species, which was because the UAV sensor provides a negative spectral response function(SRF) than WV2 in terms of the mangrove LAI estimation.